Natural occurrence of parasitoids (Hymenoptera) associated with Anastrepha fraterculus (Diptera: Tephritidae) in myrtaceae species in the northeastern province of Entre Rios, Argentina - Ovruski Alderete, Sergio Marcelo (2008)
Parasitoids of Anastrepha fraterculus (Wiedemann) were monitored on ripe fruit of 3 native and 1 exotic, wild Myrtaceae species in the Province of Entre Rios, NE Argentina, between Jan and Mar 1993 and 1994 with the aim of identifying indigenous parasitoid species and determining natural parasitization rates and fruit infestation levels. The fruit species surveyed were Psidium guajava L. (common guava), Feijoa sellowiana (O. Berg) O. Berg (feijoa), Eugenia uniflora L. (Surinam cherry), and Myrcianthes pungens (Berg) Legrand (mato). Altogether 2,186 tephritid puparia were obtained, 95% of which were A. fraterculus and 5% of which were Ceratitis capitata (Wiedemann). Of 1,667 adult insects that emerged from these puparia, 1,378 were A. fraterculus, 89 C. capitata, and 200 larval-pupal parasitoids, representing 4 species of 2 Hymenoptera families: Doryctobracon areolatus (Szépligeti), D. brasiliensis (Szépligeti), Utetes anastrephae (Viereck) (all Braconidae, Opiinae), and Aganaspis pelleranoi (Brèthes) (Figitidae, Eucoilinae). All these parasitoid species are new reports for Entre Rios. Moreover, these records represent the southernmost natural distribution range in the Americas for these species. Doryctobracon areolatus and A. pelleranoi were recovered from all of the Myrtaceae species sampled, and they were the most abundant parasitoid species. Infestation patterns by A. fraterculus in mato, Surinam cherry, guava, and feijoa varied from 15.2 to 41.8, 21.3 to 49.4, 34.1 to 109.2, and 78.9 to 140.6 larvae per kg of fruit, respectively. Highest levels of parasitism were recorded in P. guajava, whereas M. pungens had the lowest parasitization rates. However, overall mean parasitism levels (i.e., considering all parasitoid species) did not appear to have great differences when comparing Myrtaceae species, collection sites, and years. The relative abundance and parasitization rates data of the recovered parasitoids in the 4 Myrtaceae species suggest some degree of host plant preference by U. anastrephae and D. brasiliensis.